2020
DOI: 10.7764/ijanr.v47i3.2290
|View full text |Cite
|
Sign up to set email alerts
|

Physical assessment of a Mollisol under agroecological managements at Quillota valley. Mediterranean Central Chile

Abstract: A number of agroecological practices have been proposed for assessing soil quality. Several physical soil properties have been shown to be important for determining soil quality by using the sustainability index (SI) and the cumulative rating approach. The main aim of the study was to determine the effects of different agroecological managements on the physical properties of a Mollisol in the Mediterranean central Chile. In addition, some physical properties were selected to compare the soil quality among diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…They note that the greater adoption of intercropping in European agriculture requires solving technical, societal and knowledge challenges in crop production, understanding the long-term effects of diversification, and identifying and eliminating lock-ins and barriers against diversified cropping in agricultural systems. Casanova et al (2020) carried out a soil sampling survey comparing soils under industrial avocado production to those managed with agroecological practices. Using cumulative sustainability ratings for each land use, they showed that all agroecological practices constituted sustainable soil management although with high organic input requirements, while industrial avocado production was the least sustainable soil management to the extent that the authors recommended a change in land use.…”
Section: Science Innovation and Technologies In Agroecological Systemsmentioning
confidence: 99%
“…They note that the greater adoption of intercropping in European agriculture requires solving technical, societal and knowledge challenges in crop production, understanding the long-term effects of diversification, and identifying and eliminating lock-ins and barriers against diversified cropping in agricultural systems. Casanova et al (2020) carried out a soil sampling survey comparing soils under industrial avocado production to those managed with agroecological practices. Using cumulative sustainability ratings for each land use, they showed that all agroecological practices constituted sustainable soil management although with high organic input requirements, while industrial avocado production was the least sustainable soil management to the extent that the authors recommended a change in land use.…”
Section: Science Innovation and Technologies In Agroecological Systemsmentioning
confidence: 99%